A vedação da ultratividade das normas coletivas pela reforma trabalhista - Gavineski, Igor Mateus (My University, 2025)
The present study seeks to analyze the prohibition of the ultrativity of the collective norms and their effects before the principle of protection. To this end, the objective is to understand the principle of protection in the Brazilian legal system, the way in which collective norms can materialize this protection and the discussion about the application or not of ultrativity and its effects. After the amendment of TST No. 277, in 2012, being recognized the ultractivity due to compatibility with art. 114, §2º, of the CF, wording given by EC nº 45/2004, the present theme was further intensified. In a preliminary decision by Minister Gilmar Mendes, in ADPF nº 323, in 2016, the STF suspended the effects of the aforementioned statement and, in the following year, the Labor Reform (Law 13.467 / 2017) changed art. 614, §3º, of the CLT and expressly prohibited ultractivity. With the work it was demonstrated that due to these changes and several others made by the Labor Reform, the working class found itself in a delicate situation, seeing their rights being relaxed and suppressed by the simple time lapse of the expired rule, reducing their bargaining power in the face of business class. In this way, the prohibition of the ultra-activity of collective norms violates the principle of worker protection, the basic principle of Labor Law, being the same fundamental for guaranteeing the rights conquered by workers. Thus, it is necessary for the collective rules to be ultra-active, in a relative way, in order to achieve a balance between the parties in collective bargaining, giving applicability to the principle of worker protection, with its prohibition being made by art. 614, §3º, of the CLT, unconstitutional, for offense to art. 114, §2º, of the CF and the principles of worker protection. [resumo fornecido pelo autor]
O presente estudo busca analisar a vedação da ultratividade das normas coletivas e seus efeitos perante o princípio da proteção. Para tanto, objetiva-se compreender o princípio da proteção no ordenamento jurídico brasileiro, a forma com que as normas coletivas podem materializar essa proteção e a discussão acerca da aplicação ou não da ultratividade e seus efeitos. Após a alteração da súmula nº 277 do TST, em 2012, sendo reconhecida a ultratividade pela compatibilidade com o art. 114, §2º, da CF, redação dada pela EC nº 45/2004, intensificou-se ainda mais o presente tema. Em decisão liminar do ministro Gilmar Mendes, na ADPF nº 323, em 2016, o STF suspendeu os efeitos do referido enunciado e, no ano seguinte, a Reforma Trabalhista (Lei 13.467/2017) alterou o art. 614, §3º, da CLT e vedou expressamente a ultratividade. Com o trabalho ficou demonstrado que devido a essas alterações e diversas outras feitas pela Reforma Trabalhista, a classe trabalhadora se viu em uma situação delicada, vendo seus direitos serem flexibilizados e suprimidos pelo simples lapso temporal da norma vencida, diminuindo seu poder de negociação frente a classe empresarial. Desse modo, tem-se que a vedação da ultratividade das normas coletivas fere o princípio da proteção ao trabalhador, princípio basilar do Direito do Trabalho, sendo o mesmo fundamental para a garantia dos direitos conquistados pelos trabalhadores. Assim, mostra-se necessária a ultratividade das normas coletivas, de forma relativa, para haver um equilíbrio entre as partes na negociação coletiva, dando aplicabilidade ao princípio da proteção ao trabalhador, sendo sua vedação, feita pelo art. 614, §3º, da CLT, inconstitucional, por ofensa ao art. 114, §2º, da CF e aos princípios de proteção ao trabalhador. [resumo fornecido pelo autor]
Keywords: Reforma trabalhista; Princípio da proteção; Súmulas (Direito); Direito do trabalho